(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In this article is said how to use interactive methods in order to improve students’ oral speech and by using modern pedagogical and technological methods, and by the way introducing leading styles of teaching, teach growing generations, the system of speaking easily in these languages can be developed fully